The Ideal Methods for Correcting Students' Mistakes and Errors/ الأساليب المثلى في تصحيح أخطاء ومخالفات الطلاب - Khalid Hassan Alabri (Ijaz Arabi Journal of Arabic Learning, 2023)
Teaching Arabic and other subject is related to training students' skills which requires the teacher's response when students make mistakes. The goal is to correct and modify behavior. It is better to research the best methods used by teachers in correcting students’ mistakes. This paper prompts an understanding of human nature in remedying errors, such as facial expressions and body language. Also, this paper directs the teacher to use modesty as an advantage. Perhaps it will cause students to be ashamed of their errors without the teachers’ need to speak. The researcher will use a descriptive approach built on describing the phenomenon to be studied and collecting descriptions and information about it to reach results that will help acknowledge the crucial aspects of the best method to guide students and correct their mistakes. Also, extrapolate and track the means and methods by observing this matter. in verifying research, essential steps must be distinguished, attributing the verses in the Quran contained in the study to their places in the Holy Quran and extracting the hadiths from their sources. The results introduce students to the idea of error and explain they are wrong behavior by showing the teacher’s kind and encouraging words to his students and how it helps them to accept the guidance. The teacher should know when to show his anger and kindness and when to re-explain or be silent.